Behavioral Alterations in Mice Carrying Homozygous HDAC4A778T Missense Mutation Associated With Eating Disorder - Davis, Kevin C.; Saito, Kenji; Rodeghiero, Samuel R.; Toth, Brandon A.; Lutter, Michael; Cui, Huxing (Frontiers in Neuroscience, 2020)
Eating disorders (EDs) are serious mental illnesses thought to arise from the complex gene-environment interactions. DNA methylation patterns in histone deacetylase 4 (HDAC4) locus have been associated with EDs and we have previously identified a missense mutation in the HDAC4 gene (HDAC4A786T) that increases the risk of developing an ED. In order to evaluate the biological consequences of this variant and establish a useful mouse model of EDs, here we performed behavioral characterization of mice homozygous for Hdac4A778T (corresponding to human HDAC4A786T) that were further backcrossed onto C57/BL6 background. When fed high-fat diet, male, but not female, homozygous mice showed a trend toward decreased weight gain compared to their wild-type littermates. Behaviorally, male, but not female, homozygous mice spend less time in eating and exhibit reduced motivation to work for palatable food and light phase-specific decrease in locomotor activity. Additionally, homozygous Hdac4A778T female, but not male, mice display social subordination when subjected to a tube dominance test. Collectively, these results reveal a complex sex- and circadian-dependent role of ED-associated Hdac4A778T mutation in affecting mouse behaviors. Homozygous Hdac4A778T mice could therefore be a useful animal model to gain insight into the neurobiological basis of EDs.